Burden of Pneumococcal infections among under five children - Hasan, Morshed; Rabbi, Ferdous; Shahin, SM Abu; Hossain, Md Mahfuz; Jahan, Shahed (Update Dental College Journal, 2013)
Background Pneumonia is the leading cause of death for children under 5 years of age in Bangladesh. Therefore, it is important to know the impact of Streptococcus Pneumonia to avert under 5 deaths in Bangladesh. Objective The study was to assess the magnitude of Pneumococcal infections among under 5 children in a tertiary level hospital in Bangladesh. Methods It was a cross-sectional study among under 5 children who were admitted in Dhaka Shishu Hospital with respiratory infections. Purposive sampling strategy was followed and 101 children with respiratory infections were selected as required sample size for the current study. Socio-demographic characteristics, location of kitchen and nature of fuel used by the respondents, nutritional status, weight, weight for age, duration of suffering and respiratory rate of the patients were analyzed in relation to Pneumococcal infections. Results Around 30% of the sample respondents had Pneumonia, 17% had Severe Pneumonia, 26% had been affected by Meningitis and the rest had been suffering from Sepsis. Mothers higher education level had been linked up with the reduction of Pneumonia (p < .05). Additionally, mean difference of Nature of fuel used for cooking (p = .005), weight (p = .001) and weight for age (p = .001) were significantly differ among children with pneumococcal and non- Pneumococcal infection groups. Conclusion Educational status of the parents should be improved regarding overcrowding, smoke particularly during cooking and the nature of fuel. Again interventions like improved weight, weight for age and nutritional status under 5 children should be considered at a priority basis DOI: http://dx.doi.org/10.3329/updcj.v2i2.15530 Update Dent. Coll. j: 2012; 2 (2): 18-22